: Clima social escolar, desde la percepción de estudiantes y profesores del séptimo año de Educación Básica de los centros educativos urbano Charles Darwin y rural Augusto Arias de la Ciudad de Santo Domingo de los Colorados, provincia de Santo Domingo de los Tsáchilas en el año lectivo 2012-2013 - Leon Obando, Nela Katerine (2013)
The study of educational management and social climate of the classroom are factors of quality education in our country by what is made efforts to change them and improve them. This research aims to know the teaching and the social climate of the classroom, as elements of measurement and description of the environment in which the educational process of the students of the seventh year of basic education develops. Thus there has been a study in the province Santo Domingo de los Tsáchilas in fiscal institutions urban "Charles Darwin" and rural "Augusto Arias" with a sample of 30 and 12 students and two teachers. The methods used were the analytic, synthetic, inductivo-deductivo, statistical and hermeneutic, the techniques are bibliographic research and field and instruments such as questionnaires for students and teachers. In conclusion is needed training, and budget to create an environment with a better coexistence between the members of the educational community. For this reason it invites the reader to read this research with a view to changing the classroom environment.